Representasi Tindakan Sosial dalam Tradisi Lokal Masyarakat di Era Modern - Karina Puji Lestari; Dany Miftah M. Nur; Abdul Karim (IAIN Madura, 2025)
Local traditions that persist amid changing times reflect deep social meanings embedded in cultural practices. One such tradition is Sewu Sempol, a grave-offering ritual carried out by the people of Hamlet Masin, Kandangmas Village, Kudus, every last Thursday of the month of Ruwah (Sya'ban). This study aims to describe the implementation of the tradition and analyze it using Max Weber’s theory of social action. The research method used is qualitative with a phenomenological approach. Data analysis techniques include data collection, data reduction, presentation of findings, and drawing conclusions. Data were collected through direct observation, in-depth interviews with community leaders and local residents, as well as visual documentation. Data sources were obtained from active participants in the tradition and relevant literature. The findings show that people carry out this tradition as traditional action, since it is inherited through generations; as goal-oriented action, in hope of safety and blessings; as value-oriented action, because it is considered morally and spiritually noble; and as affective action, driven by emotions of gratitude and reverence for ancestors. These four types of social action form a complex social meaning behind the preservation of the Sewu Sempol tradition within the community.